Gingival thickness assessment at the mandibular incisors with four methods: A cross‐sectional study. Issue 11 (20th August 2018) - Kloukos, D.; Koukos, G.; Doulis, I.; Sculean, A.; Stavropoulos, A.; Katsaros, C.
Abstract: Background: This study was conducted to determine accuracy, precision and repeatability of four different methods for assessing gingival thickness Methods: This cross‐sectional study evaluated gingival thickness on 200 consecutively included orthodontic patients. Gingival thickness was assessed at both central mandibular incisors with: 1) transgingival probing with a standard periodontal probe, 2) transgingival probing with a stainless‐steel acupuncture needle, 3) ultrasound, and 4) a color‐coded periodontal probe. Intra‐examiner reproducibility and method error were also evaluated. Results: Transgingival measurements with the standard periodontal probe were found to be more accurate than those with the acupuncture needle, after method error assessment. Acupuncture needle and ultrasound device yielded higher values than the probe. Expected differences between the two methods were 22% more for the mandibular left central incisor (95% confidence interval (CI) = 11% to 32%) and 26% more (95% CI = 13% to 39%) for the mandibular right central incisor when measured with the needle. Ultrasound measurements exceeded probe measurements on average by 0.16 mm at mandibular left central incisor (95% CI = 0.14 to 0.18) and by 0.11 mm for mandibular right central incisor (95% CI = 0.08 to 0.13). Intraclass correlation coefficient concluded good agreement for the color‐coded periodontal probe (0.624). Conclusions: Within the inherent limit of the uncertainty about the true value of gingival thickness, the present results demonstrate the differences between the tested methods, as far as accuracy and reproducibility are concerned. Based on the reproducibility, the transgingival probing with the periodontal probe as well as the ultrasound determination, seem to present an adequate choice for every day practice.